TREATMENT OF AL-DIWANIYAH REFINERY WASTEWATER USING KARBALA CLAY-BASED CERAMIC MEMBRANES - Adyan Yahya Ghanim; H.I.Dawood; Haider Alaa Maabed (Journals Park Publishing, 2025)
This study aimed to fabricate and characterize a new flat ceramic membrane using Karbala clay and wood sawdust via a disc casting method for microfiltration applications. The membrane sintered at 1050 °C for 3 hours exhibited a porosity of 53.76%, pore size ≈1.45 μm, and water permeability of 183.76 L/h·m²·bar. Performance evaluation using wastewater from the Al-Diwaniyah refinery under of 1–2 bar, 30–40 °C, and 30–60 L/h flow rate. The results showed that the system achieving up to 96% turbidity removal at 2 bar, 40 °C, and 45 L/h, with a moderate reduction in Chemical Oxygen Demand (COD) and Total Dissolved Solids (TDS). The treated water pH increased from 7.4 to 8.1, indicating alkalinity interactions with the ceramic surface. These findings demonstrate that locally fabricated ceramic membranes provide a cost-effective and eco-friendly solution for industrial wastewater treatment, with potential for further design optimization.
Keywords: Karbala clay, Sawdust, Ceramic membrane, Microfiltration, Industrial wastewater treatment, Al-Diwaniyah refinery.